Realism in the Trans ASEAN Gas Pipeline Project - Syah, Rahmadha Akbar; Mahmud, Zaki Khudzaifi (Indonesian Journal of Energy, 2019)
To improve connectivity and energy security, especially natural gas, Southeast Asian countries, under the cooperation of Association of Southeast Asian Nations (ASEAN), are trying to build a gas pipeline that stretches from Indonesia to Myanmar. The project is called the Trans ASEAN Gas Pipeline (TAGP) under the ASEAN Plan of Action for Energy Cooperation (APAEC) scheme. However, regional countries are still dealing with their domestic problems, and there are fears that TAGP is detrimental to producer countries, resulting in the delay of this project as much by as four years – from 2020 to 2024. The uncertainty of the TAGP project further emphasizes that there is a tendency for countries not to adhere to the ASEAN forum’s agreements. Especially if it has to be juxtaposed with the Russian Gas Pipeline project which was built to distribute natural gas to Western European countries, TAGP is still far behind. In designing this paper, the authors use qualitative methods through literature studies by referring to the realism approach of International Relations to dissect TAGP problems. Furthermore, the author also feels the need to accommodate the neorealism approach to be used as a supportive approach in looking at the issues of disobedience in regional countries in supporting the TAGP scheme. Also, the authors conducted a brief comparison between TAGP and the Russian Gas Pipeline to be used as a case study analysis material that would later provide answers of why TAGP failed to go as planned.